16S ribosomal RNA of Escherichia coli contains a N2-methylguanosine at 27 nucleotides from the 3' end. - Van Charldorp, R (1981)
The 49 nucleotides fragment derived from the 3' end of 16S rRNA by cloacin DF13, is not cleaved by ribonuclease T1 at a guanosine residue tha is present at 27 nucleotides from the 3' terminus (position 115 in 16S rRNA). Analysis of the isolated nucleotide indicates that it is a modified G residue. In vivo labeling with (3H)methionine shows that this G is methylated and co-chromatography with markers reveals that it is N2-methylguanosine.